2022
DOI: 10.3390/biomedicines10071634
|View full text |Cite
|
Sign up to set email alerts
|

Androstenedione and Follicle-Stimulating Hormone Concentration Predict the Progression of Frailty Syndrome at One Year Follow-Up in Patients with Localized Breast Cancer Treated with Aromatase Inhibitors

Abstract: Background: The standard treatment in postmenopausal women with estrogen- and progesterone-positive localized breast cancer consists of aromatase inhibitors (AROi). The ability of AROi to promote or worsen frailty syndrome over time and the relationship with changes in gonadal hormones concentration in blood have not been investigated. Methods: A prospective study to evaluate the relationship between frailty syndrome and gonadal hormones concentrations in blood at baseline (prior to AROi treatment) and after 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Consequently, the premise is raised that the inhibition of aromatase activity in patients could trigger an increase in androstenedione production. The results of a longitudinal study, carried out in patients with breast cancer undergoing hormonal treatment with aromatase inhibitors, support this idea [23]. There was a significant increase in the plasma levels of androstenedione due to the inhibition of aromatase activity, which highlights the importance of this enzyme in the regulation of hormone synthesis.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Consequently, the premise is raised that the inhibition of aromatase activity in patients could trigger an increase in androstenedione production. The results of a longitudinal study, carried out in patients with breast cancer undergoing hormonal treatment with aromatase inhibitors, support this idea [23]. There was a significant increase in the plasma levels of androstenedione due to the inhibition of aromatase activity, which highlights the importance of this enzyme in the regulation of hormone synthesis.…”
Section: Discussionmentioning
confidence: 82%
“…At the time of the study, 63% of the patients had undergone a prostatectomy, and 37% had not. The mean BMI of the participants was 27.7 ± 0.42 (SEM; range: [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and according to these data, 23.1% of the patients had a normal weight (BMI = 18.5-24.9 kg/m 2 ), 55.4% were overweight (BMI = 25-29.9 kg/m 2 ), and 21.5% were obese (BMI > 30 kg/m 2 ). None of the patients were underweight (BMI < 18.5 kg/m 2 ).…”
Section: Sociodemographic and Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other studies have also found significant correlations between androstenedione and other diseases. For example, Javier et al 33 found that androstenedione can predict the progression of Frailty Syndrome in patients with localized breast cancer treated with aromatase inhibitors. Adriaansen et al 34 reported that diurnal salivary androstenedione levels in healthy volunteers for monitoring treatment efficacy of patients with congenital adrenal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical research reveals valuable information on human diseases by employing in vitro and in vivo models [ 25 , 26 , 27 , 28 ]. Data collected in-laboratory has made significant contribution to understanding the pathomechanism of human diseases from molecular to organismal levels in search of therapeutic targets [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Here, we highlight clinical studies of common pathogenic factors in migraine and NP with reference to preclinical data to explore potential therapeutic targets and clarify the current missing data for it to be complemented in the near future, in search of innovative pain management in migraine and NP.…”
Section: Introductionmentioning
confidence: 99%